2020
DOI: 10.1016/j.jaci.2019.10.030
|View full text |Cite
|
Sign up to set email alerts
|

Protein-coding variants contribute to the risk of atopic dermatitis and skin-specific gene expression

Abstract: Background: Fifteen percent of atopic dermatitis (AD) liability-scale heritability could be attributed to 31 susceptibility loci identified by using genome-wide association studies, with only 3 of them (IL13, IL-6 receptor [IL6R], and filaggrin [FLG]) resolved to protein-coding variants. Objective: We examined whether a significant portion of unexplained AD heritability is further explained by low-frequency and rare variants in the gene-coding sequence. Methods: We evaluated common, low-frequency, and rare pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 42 publications
2
24
0
Order By: Relevance
“…Another multi-omic approach included a highly diverse patient collective to investigate low-frequency and rare-coding variants associated with AD to improve the understanding of disease heredity. Through this in-depth view, they found a new and potentially therapeutic target comprising the surface receptor CD200R1 and its associated adaptor protein DOK2 [49].…”
Section: Ups and Downs Of Skin Molecular Profilingmentioning
confidence: 99%
“…Another multi-omic approach included a highly diverse patient collective to investigate low-frequency and rare-coding variants associated with AD to improve the understanding of disease heredity. Through this in-depth view, they found a new and potentially therapeutic target comprising the surface receptor CD200R1 and its associated adaptor protein DOK2 [49].…”
Section: Ups and Downs Of Skin Molecular Profilingmentioning
confidence: 99%
“…An extension to GWAS, focusing on protein-coding variants, used exome genotype and skin transcriptome data (Mucha et al, 2019). This study identified an additional 12% of AD heritability explained by rare protein-coding variation in genes including IL4R, IL13, JAK1, JAK2 and TYK2, as well as novel candidate genes DOK2 and CD200R1.…”
Section: Gwas Applied To Atopic Dermatitismentioning
confidence: 99%
“…GWAS findings to date account for <20% of AD heritability (Paternoster et al, 2015) and even with the additional risk attributed to protein-coding variants, ~70% of heritability remains to be explained (Mucha et al, 2019). Considerable further work is therefore needed to fully understand individual risk.…”
Section: Outstanding Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Current estimates of heritability explained by common AD susceptibility variants (minor allele frequency MAF≥1%) amount to 14.91%. An additional 12.56% of heritability are estimated to be attributable to rare protein-coding variants (MAF<1%) ( 21 ).…”
Section: High-throughput Sequencing Provides New Insight On the Genetmentioning
confidence: 99%